The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/antiox10060880
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation in Diazotrophic Bacteria in Interaction with Plants

Abstract: Plants interact with a large number of microorganisms that greatly influence their growth and health. Among the beneficial microorganisms, rhizosphere bacteria known as Plant Growth Promoting Bacteria increase plant fitness by producing compounds such as phytohormones or by carrying out symbioses that enhance nutrient acquisition. Nitrogen-fixing bacteria, either as endophytes or as endosymbionts, specifically improve the growth and development of plants by supplying them with nitrogen, a key macro-element. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 146 publications
(188 reference statements)
0
16
0
Order By: Relevance
“…Due to their features and quantity (production and disposal) inside cells, ROS are recognized as universal signaling chemical species [ 131 ]. ROS, either associated with abiotic stresses or produced by host plants, determine the outcome of the plant-bacteria interaction [ 132 ], e.g., the optimal formation of legume-rhizobial interaction, especially in the development of symbiosis [ 131 ]. It is speculated that a high level of polyphenol oxidase activity in N 2 -fixing nodules relates to the similarity of the response of plants to pathogens since the protective responses of legume plants to the invasion of rhizobia are analogous to the pathogenic process [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their features and quantity (production and disposal) inside cells, ROS are recognized as universal signaling chemical species [ 131 ]. ROS, either associated with abiotic stresses or produced by host plants, determine the outcome of the plant-bacteria interaction [ 132 ], e.g., the optimal formation of legume-rhizobial interaction, especially in the development of symbiosis [ 131 ]. It is speculated that a high level of polyphenol oxidase activity in N 2 -fixing nodules relates to the similarity of the response of plants to pathogens since the protective responses of legume plants to the invasion of rhizobia are analogous to the pathogenic process [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed decrease in phenylpropanoids, carotenoids, and xanthophylls may lead to oxidative stress of the plant but also of the interacting bacteria. Those bacteria may therefore deal with higher oxidative stress that may influence the efficiency of their interactions with their host, as previously described [ 59 ]. Moreover, carotenoids and xanthophylls are precursors of abscisic acid (ABA), a phytohormone involved in plant–bacteria interactions [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are mostly legume–diazotroph interaction-specific and needed for the legume seedlings to get activated during the initiation of the symbiotic association. Glutathione metabolism-related pathway is related to ROS-scavenging during diazotrophic interaction and nodulation ( Mandon et al., 2021 ); amino acid metabolism (biosynthesis, transport, and/or degradation) and are often crucial for the establishment and maintenance of an effective nitrogen-fixing symbiosis process, which is intimately interconnected with the metabolism of the plant ( Dunn, 2014 ); nitrogen signaling and metabolism ( Carvalho et al., 2014 ); and symbiosome-related pathways (phagosome). It is reported that the root cells accommodate the rhizobia by the suppression and defunctionalization of their vacuole and also by retargeting some tonoplast proteins to symbiosome ( Gavrin et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%